Acute myocardial infarction in the postpartum period in the young woman with protein C deficiency - E. S. Eniseeva; K. V. Protasov; Y. A. Reut; O. M. Senderova; N. V. Shcherbakova; N. V. Petronchak (Acta Biomedica Scientifica, 2018)
Women of childbearing age without cardiovascular risk factors have low risk of acute myocardial infarction. Pregnancy has been shown to increase the risk of myocardial infarction compared to the risk in non-pregnant women of similar age. Acute myocardial infarction during pregnancy or postpartum period as a rule develops due to coronary spasm or non-atherogenic thrombosis or spontaneous coronary dissection. Thrombosis is most likely related to hypercoagulable state of pregnancy and postpartum period. It is worth considering the importance of defects of coagulation, such as Leiden factor, protein C, protein S, antithrombin III and mutations of propter genes. There is also the significant role of antiphospholipid antibodies in young women. We present the clinical case of acute ST-elevation myocardial infarction in 34-years old woman without traditional cardiovascular risk factors, which was developed after childbirth due to non-atherogenic left anterior coronary artery thrombosis. Her coagulation profile showed normal results for antithrombin III, protein S, prothrombin gene mutation, factor V Leiden and antiphospholipid antibody syndrome. At the same time the protein C activity decreased to 43 % as well as trombophilia genetic markers MTHFRC677T, MTRR 66A>G, ITGA2:807 C>T and ITGB:1565 T>C genetic polymorphisms were revealed.